(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Online shopping trend is extremely common now days. This process takes a medium for purchasing goods and services which is internet. You will find numerous elements which can affect consumer’s online purchasing behavior. These elements could differ from individual to individual. Online users in Bangladesh have risen rapidly during the last few years. Marketers are using this pattern by opening up online outlets to entice buyers to shop online. Nevertheless, translating internet users to online buyers remains challenging for marketers. The goal of this analysis is analyzing things affecting on online shopping behavior of customers that could be just about the most crucial issues of e commerce and advertising field. The goal of this paper is reviewing the current literature to be able to determine the different major specific factors which effect customer’s goal to shop online for electronics goods and suggest an integrated design which will describe the buyer’s intention to follow internet shopping. This report examines the outcome of 7 factors on consumers’ confidence in online buying electronic items and technology.